Respostas
respondido por:
8
a) 5(-x +1) +2(3x -4) -1
-5x +5 +6x -8 -1
-5x +6x= 1+ 8 -5
x= 9 -5
x= 4
b) x+4 /3 -3x-2 /4 ≥ 0
mmc entre 4 e 3 ≥12
divide pelo denominador e multiplica pelo numerador.
4x+16-9x-6 /12 ≥ 0
-5x +10 /12 ≥0
-5x +10 ≥ 12.0
-5x +10≥ 0
-5x ≥ -10 (-1)
5x≥ 10
x= 10/5
x= 2
-5x +5 +6x -8 -1
-5x +6x= 1+ 8 -5
x= 9 -5
x= 4
b) x+4 /3 -3x-2 /4 ≥ 0
mmc entre 4 e 3 ≥12
divide pelo denominador e multiplica pelo numerador.
4x+16-9x-6 /12 ≥ 0
-5x +10 /12 ≥0
-5x +10 ≥ 12.0
-5x +10≥ 0
-5x ≥ -10 (-1)
5x≥ 10
x= 10/5
x= 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás